Comprehensive phenotyping and genotyping of a large diverse panel of the wheat wild relative, Aegilops tauschii for wheat streak mosaic virus tolerance - Prakash, Ved; Adhikari, Laxman; Poland, Jesse; Nouri, Shahideh (Frontiers in Microbiology, 2026)
The wheat streak mosaic (WSM) complex, primarily caused by wheat streak mosaic virus (WSMV) and Triticum mosaic virus (TriMV), results in significant annual yield losses in the northern plains of the United States. Wheat wild relatives, including Aegilops tauschii, represent valuable resources of genetic diversity, including resistance to pathogens. In this study, we report the first comprehensive phenotypic assessment and genome-wide association study (GWAS) of a geographically diverse panel of 250 Ae. tauschii accessions for WSMV tolerance in single and mixed infections with TriMV. Phenotyping for WSMV symptom severity and quantitative polymerase chain reaction (qPCR)-derived viral titers identified 124 tolerant genotypes in single infections. In double-infection assays, 22 of 39 tested accessions, including both WSMV-tolerant and susceptible genotypes, exhibited tolerance to both viruses. The GWAS revealed that 12 genomic loci were significantly associated with WSMV severity and 8 loci were associated with the viral titer in single infections. Notably, a large effect locus for symptom severity mapped to the long arm of chromosome 5D within lineage two (L2) at 432 Mb. Additional loci in the same region, also identified by the BLINK model, were detected at 430 Mb and 529 Mb. These regions harbor multiple previously reported disease resistance-related genes. These findings suggest that tolerance to WSMV in Ae. tauschii is controlled by multiple quantitative trait loci (QTL), highlighting the need for further validation and functional characterization. The WSMV-tolerant germplasm identified in this study constitutes a valuable genetic resource for incorporation into wheat improvement programs. This work lays the foundation for the functional characterization of WSMV tolerance loci in Ae. tauschii and provides a framework for leveraging genetic diversity for improving virus resistance in wheat through marker-assisted breeding strategies.